Inequality degree within the country in the context of realising the Sustainable Development Goals - L. A. Davletshina; M. S. Telyuk; N. A. Sadovnikova (Вестник университета)
The article assesses the inequality degree within Russia in the context of realising the Sustainable Development Goals. The review of foreign and domestic scholarly writings, focusing on current issues of implementation and achievement of the Sustainable Development Goals, is presented. The authors reviewed the indicators development degree of sustainable development in Russia as of December 2021. It is determined that Goal 3 “Ensure healthy lifestyles and promote well-being for all at all ages” is the most fully disclosed. Based on the National Indicators of Goals 3, an original system of statistical indicators for assessing inequality between regions has been compiled and substantiated. According to the indicators presented in the above-mentioned system, the clustering procedure of the Russian regions was carried out, and the assessment and interpretation of the selected clusters were given. The content distribution into typological groups was practically not influenced by territorial affiliation. A significant role was played by direct indicators, included in the indicator system, and indirect factors, affecting both the development of the region and the socio-economic well-being of the inhabitants of these regions. The authors believe that there remains relevant to study the transformations that the two divergent flows will take place in the coming years: 1) existing national projects and state programmes to solve the tasks and achieve the planned values formulated in the National Set of Sustainable Development Goals Indicators in the part of Goal 3; 2) the current epidemiological situation, which in the period 2020–2021 has already made tangible changes in the size and composition of the population.